Rancang Bangun Game Edukasi â€œKuy Ngajiâ€ Berbasis Android Menggunakan Metode Finite State Machine - Haqiqi Tegar Sanubari, Ahmad; Putra Eka Prismana, IGL; Kistofer, Terdy (Inovate, 2021)
Kuy Ngaji game application is an application used to support learning programs to write and hear the pronunciation of hijaiyah letters. This application can be supported by the smartphone as a tool to play the game. The purpose of this study is to design and build an educational application that is educational to children for learning hijaiyah letters writing and how to pronounce them. The method in this study uses the Finite State Machine as a game flow determination. Application of flood fill as an algorithm connecting one node to another node aims to support the process in the game. The results of this research is where the player will write hijaiyah letters in the game, the more perfect the player writes the letters, the point will be perfect. Point in the game is a star that will be obtained, the maximum number of stars is 3 stars. Keywords : Finite State Machine, Flood Fill, Education Game.